Testing and assessment in counselling - Eric Atta Quainoo; Joana Bortey; Evans Austin Brew; Isaac Pinamang (International Journal of Educational Innovation and Research, 2022)
Counselling has developed in recent years into a humanistic partnership in problem solving and growth. Consistent with this development is the client's participation in decisions regarding all aspects of the counselling relationship. Testing and assessment need to be included here. In this regard, clients need to realize that tests are no more than instruments for furnishing information about themselves, as well as a guide for the counselling process and future decision making. Ultimately, test use by counsellors must be seen as an adjunct to the entire counselling process. Test results provide descriptive and objective data which help the counsellor to assist clients better in making the choices that will affect their lives. In order to make the best use of available tests in a counselling relationship, the process of testing and the issues which surround the process must be examined.